2007
DOI: 10.1080/10245330600954056
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic cytogenetic markers in childhood acute lymphoblastic leukemia: Cases from Mansoura Egypt

Abstract: The objective of the work was to evaluate children with acute lymphoblastic leukemia (ALL) showing resistance to immediate induction chemotherapy in relation to conventional and advanced cytogenetic analysis. The study was conducted on 63 ALL children (40 males and 23 females) with age range 4.5 months-16 years (mean = 7.76 years). They included 37 cases who attained a true remission and 26 complicated by failure of remission, early relapse or death. They were subjected to history, clinical examination and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…Low hypo-diploid karyotype (30-44 chro mosomes) were present in 12% of the our cases, which are h igher than those reported by others who considered hypo-diploidy to be a relatively uncommon (>9%) finding in ALL [17,18]. Many studies reported low percent of patients in hypo-diploid group, but some studies [19][20], including our study (12%) found much higher percent of the patient in this group with good remission. In studies in which only cytogenetic investigations are carried out, some hypo-diploid cells may not diagnosed correctly due to presence of many hyper-diploid cells and only after relapse of the disease and repeat investigation of these patients with FISH, or other advanced molecular methods, the true karyotype can be detected.…”
Section: Discussioncontrasting
confidence: 49%
“…Low hypo-diploid karyotype (30-44 chro mosomes) were present in 12% of the our cases, which are h igher than those reported by others who considered hypo-diploidy to be a relatively uncommon (>9%) finding in ALL [17,18]. Many studies reported low percent of patients in hypo-diploid group, but some studies [19][20], including our study (12%) found much higher percent of the patient in this group with good remission. In studies in which only cytogenetic investigations are carried out, some hypo-diploid cells may not diagnosed correctly due to presence of many hyper-diploid cells and only after relapse of the disease and repeat investigation of these patients with FISH, or other advanced molecular methods, the true karyotype can be detected.…”
Section: Discussioncontrasting
confidence: 49%
“…In this regard, experiments on miRNA have shown that a single miRNA can play a role in both heart formation and function (( 26), ( 27), ( 28), ( 29)). In the zebrafish (Danio rerio), research has also shown that miRNAs regulate cardiac production by regulating TBX2, CSPG2, and NOTCH1 (30,31). Overall, these findings highlight the several roles that miRNAs play in cardiac growth.…”
Section: The Function Of Micrornas In the Formation Of The Heartmentioning
confidence: 77%
“…False negative rate for G6PD screening is about 4%. 11 If analysis of G6PD is done during, or just after, a hemolytic episode, the result could be falsely normal. In such cases, the analysis has to be done after 90 to 120 after resolution of hemolysis or when there is high clinical suspicion of G6PD, it's recommended to consider sequence analysis of G6PD gene.…”
Section: Discussionmentioning
confidence: 99%